OP0062 The fully human anti-tnf antibody adalimumab (d2e7) in combination with methotrexate (mtx) in the treatment of active rheumatoid arthritis: results of a 2-year study. (1st June 2001) - Breedveld, FC; Allaart, CF; Rau, R; Herborn, G; Wassenberg, S; Kroot, EJ; Van Riel, PL; Van de Putte, LB; Böger, C; Schattenkirchner, M; Kempeni, J; Beck, K; et al.
Abstract : Background: Objectives: To evaluate the long-term efficacy and safety of a combination of methotrexate (MTX) with the fully human anti-TNF antibody adalimumab (D2E7) in patients with active rheumatoid arthritis (RA). Methods: 54 patients, who were partial responders to standard doses of MTX (mean 16 mg/week), were included in this randomised double blind, placebo-controlled study (DE010). Initially, patients were randomised into three treatment arms of 18 patients each and then injected double blind (first and second injection) with either 1 mg/kg adalimumab i.v., 1 mg/kg adalimumab s.c., or placebo (double dummy). Thereafter, all patients received open-label s.c. injections of 1 mg/kg adalimumab. The frequency of administration (every other week up to every other month) depended on the individual response to treatment. Results: The overall efficacy results for the open label period of 24 months are summarised in the Table 1 below. Adverse events were well matched between both adalimumab treatment arms and placebo during the initial double blind study period. A total of 44 patients (81%) were able to complete the 2-year study period. Reasons for drop out were adverse events (6 pts), lack of efficacy (2 pts), death (1 pt, myocardial infarction), and protocol violation (1 pt). Conclusion: Repeated subcutaneous injections of 1 mg/kg adalimumab (D2E7) over a period of two years showed sustained efficacy and were well tolerated when given in combination with stable standard doses of MTX to patients with active RA.